Analysis Of User Satisfaction On Edmodo And E-Learning In Higher Education Student Using Kano Method - Pranata, Erika; Sutoyo, Mochammad Arief Hermawan; Veronica, Sheila; Natalie, Sherly; Wijaya, Tiara Vinsky; Mahendra, Vimaladevie (MASE - Media Applied and Engineering, 2024)
The Edmodo application and E-learning are learning facilities at University Y in Jambi to anticipate face-to-face learning that has the potential to increase the spread of the virus through direct/face-to-face interactions between lecturer and student. The purpose is to present the value from user satisfaction, determine the effect of application quality and provide suggestions regarding the Edmodo application and university Y E-learning to increase user satisfaction. The method used by the author is the Kano method. Kano's method is a method that identifies user needs and expectations through preference classification techniques. The purpose of the Kano method is to classify the attributes of a product or service by looking at the level of satisfaction and fulfillment of customer needs for the product or services offered. The data was taken by distributing questionnaires made with google forms which have been distributed online and got 58 respondents who are users of the Edmodo application and university Y E-learning. The results of calculations between these two e-learning applications are in the Indifferent phase which means these customers are indifferent to the feature, and do not care about the presence of the feature so that it does not make a significant difference in product satisfaction reaction. In the Edmodo application, students were most satisfied in the easy-to-learn application category and most dissatisfied in the satisfactory display category. As for the university Y E-learning, students were most satisfied in the trustworthy privacy category and the least satisfied in the recommended category.